Monstrous Bodies and Subversive Errors: Монструозни тела и субверзивни грешки - Gržinić, Marina; Tasev, Saše (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Marina Gržinić | Марина Гржиниќ Title (English): Monstrous Bodies and Subversive Errors Title (Macedonian): Монструозни тела и субверзивни грешки Translated by (English to Macedonian): Saše Tasev | Саше Тасев Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 164-183 Page Count: 19 Citation (English): Marina Gržinić, “Monstrous Bodies and Subversive Errors,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 164-183. Citation (Macedonian): Марина Гржиниќ, „Монструозни тела и субверзивни грешки“, превод од англиски Саше Тасев, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 164-183.